2003
DOI: 10.1098/rspa.2002.1018
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of lubricant–film thickness using ultrasound

Abstract: Ultrasound is re®ected from a liquid layer between two solid bodies. This re®ection depends on the ultrasonic frequency, the acoustic properties of the liquid and solid, and the layer thickness. If the wavelength is much greater than the liquid-layer thickness, then the response is governed by the sti¬ness of the layer. If the wavelength and layer thickness are similar, then the interaction of ultrasound with the layer is controlled by its resonant behaviour. This sti¬ness governed response and resonant respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
151
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(154 citation statements)
references
References 16 publications
(17 reference statements)
1
151
0
2
Order By: Relevance
“…There are several methods to do this. One could be to use ultrasonic film measurement (see for example [38]) and the other would be ellipsometry (an optical technique for investigating the dielectric properties of thin films, see for example [39]). …”
Section: Discussion Of Modellingmentioning
confidence: 99%
“…There are several methods to do this. One could be to use ultrasonic film measurement (see for example [38]) and the other would be ellipsometry (an optical technique for investigating the dielectric properties of thin films, see for example [39]). …”
Section: Discussion Of Modellingmentioning
confidence: 99%
“…Dwyer-Joyce et al [9] demonstrated that this relationship held for typical lubricant film thickness in the hydrodynamic and elastohydrodynamic regime. This approach has subsequently been used for the measurement of oil film thickness in power station thrust bearings [10], hydrodynamic journal bearings [11], a rolling element bearing [12], and a hydraulic motor piston ring/liner [13].…”
Section: Introductionmentioning
confidence: 99%
“…The measured film thickness was displayed in real time on the PC (reflection coefficient spectra, pulse amplitudes, and film thickness data are stored for post-processing). This method is described in more detail in references [9,10].…”
Section: Ultrasonic Measurement Of Oil Filmsmentioning
confidence: 99%
“…A promising technique for the monitoring of fluid film thickness is that using the reflection of longitudinal ultrasonic waves [9]. In common with shear reflection, this can be used on original bearing parts and does require any contact with the liquid film.…”
Section: Introductionmentioning
confidence: 99%